Interprofessional identity in clinicians: A scoping review. - Wood, Angela; Copley, Jodie; Hill, Anne; Cottrell, Neil (Journal of Interprofessional Care)
Interprofessional collaborative practice (IPCP) has been recognized as invaluable in delivering safe, high-quality patient care with finite resources. However, despite a decade of advances in interprofessional (IP) research, policy, and competency frameworks, IPCP does not always occur in practice. One reason may be the influence of a clinician's identity in an IP context. The purpose of this scoping review was to understand the nature of IP identity in healthcare clinicians. The PRISMA framework was used to support a comprehensive search strategy and screening of 1746 articles. Inclusion criteria included original research, theses, and reviews, a primary focus on IP identity or professional identity (PI) in an IP team, and a focus on health professionals, including students transitioning to practice. Ninety-five papers met the eligibility criteria, though once charted, just four of the 95 papers focused on IP identity in clinicians. Three further papers examined shared team identity, 25 papers referred to, but did not focus on IP identity, and the remaining 63 papers explored PI in an IP team. While limited studies on clinician IP identity restrict conclusive findings, patterns were identified to direct further research on the nature of IP identity in clinicians. These include values and beliefs, individual and personal factors, profession and professional experience, education, socialization, context, leadership, and the process of IP identity development. While identity is undeniably central to being a clinician, the values, beliefs, attributes, and experiences that contribute to clinician IP identity, how clinician IP identity develops, and factors that influence IP identity remain unclear. The results of this review highlight the value of further investigation of the nature of IP identity, the interplay between PI and IP identity, and identity in an IP context.